Kāmāyanī : Śabdānukramaṇikā : kavivara Jayaśaṅkara Prasāda kr̥ta Kāmāyanī kī śabdānukramaṇikā - Snatak, Vijayendra, 1914-; Tivārī, Bholānātha, 1923-1989 (Kendrīya Hindī Nideśālaya [Bhārata Sarakāra], 1970)
Concordance to the Kāmāyanī, poetical work of Jai Shankar Prasad, 1889-1937, Hindi poet.